A behavioral portfolio analysis of retirement portfolios - Nico Singer (Universität Rostock, Institut für Volkswirtschaftslehre, 2009)
With regard to retirement savings individual investors tend to hold large positions of their wealth in riskless assets, although equity products offer higher returns. In this article we study a behavioral portfolio model which captures this phenomenon by considering two behavioral aspects: fear and hope. In detail, we extend Shefrin's and Statman's stochastic behavioral portfolio model [SS00] and provide an equivalent deterministic model, which can be solved numerically. This allows us to apply this behavioral portfolio model even to a large amount of return data of retirement assets. When we assume fear, we find an optimal retirement portfolio with large positions in riskless assets. In this case, the proportion invested in equity is very small up to zero, while it is large when we assume hope. In short, a fear-driven behavior results in a smaller expected portfolio return and a shifting of wealth from risky to riskless assets; a hope-driven behavior results in a larger expected portfolio return and a shifting of wealth from riskless to risky assets.
Keywords: G11; 330; behavioral portfolio choice; decision making under risk; retirement portfolios; Private Rentenversicherung; Anlageverhalten; Portfolio-Management; Entscheidung bei Risiko; Schätzung; D